Estudo clínico e histopatológico dos efeitos da radiação ionizante com dose subletal em camundongos - Igor de Campos Fontes (2022)
Ionizing radiation has been used in various disease treatments, mainly in the oncology area, proving to be an interesting tool alongside chemotherapy for the cure or palliative treatment of patients. On the other hand, radiation can also be used as a weapon of mass destruction, which generates radioactive compounds that are difficult to trace, preventing adequate clinical control of patients. Exposure to radiation, accidental or presumed by radiotherapy, can generate side effects, characterized by the so-called acute radiation sickness and treatments aimed at radiation-induced injuries depend on the symptoms, the dose of exposure as well as the tissue irradiated. Due to the diverse possibilities of exposure to radiation and the varied forms of presentation of diseases caused by radiation, experimental models capable of mimicking some of these situations are important study tools. In this context, the animal model of radiation disease used in this study evaluated the effects of exposure on the entire body of C57BL/6 mice, during a period of approximately 30 days after lethal (7 Gray) and sublethal (5 Gray) doses at a rate dose of 0.75 min1 of Gamma rays. The clinical data analyzed were: temperature and body weight, mucosal changes and food consumption. The anatomopathological analyzes were performed on the following organs: intestine, lung and bone marrow in the 5 Gy groups and the control group without irradiation at the end of 30 days. Clinically, it was observed that the survival of the 7 Gy group was reduced up to 11 days post-irradiation and the animals in the 5 Gy group survived approximately 30 days after irradiation. Changes in mucous membranes and extremities (paws and snout) were more frequent in the 7 Gy group of animals compared to animals in the 5 Gy group. Bone marrow analysis demonstrated hypoplasia of hematopoietic progenitors and an increased number of adipocytes in the 5 Gy group. In the lung, an intense inflammatory process with thickening of the alveolar septum was observed after 30 days of irradiation. In the intestine, the goblet cells, as well as the architecture of the colon, were preserved and without changes to the crypts or mucosa at the end of the experiment.